2019
DOI: 10.3390/su11215910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Spatial Disparity of Access to Public Parks in Gated and Open Communities with an Improved G2SFCA Model

Abstract: A major concern of social equity and environmental justice is whether urban green resources are equitably distributed across the compact megacities of China. Many previous studies have evaluated the disparities in park access among various social groups, but few researchers have considered the heterogeneity of the built environment in residential communities. This study revisits an increasingly popular Gaussian-two-step floating catchment area (G2SFCA) model and mainly improves its two core parameters, the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The accessibility to green spaces is an important assessment factor when evaluating the distributive spatial effects green spaces on quality of life. A set of accessibility measurement approaches are defined to assess the accessibility, such as ‘container’ measurement, ‘coverage’ measurement,’ minimum distance’ approach, ‘travel (summarised by Zhang et al, 2019 ), and ‘residential proximity’ metrics and ‘cumulative opportunity’ metrics (reviewed by Ekkel and de Vries, 2017 ). Ekkel and de Vries (2017) address the association between the green space accessibility metrics and the health aspects, and they conclude that the green spaces within a walkable distance have a positive effect on human health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The accessibility to green spaces is an important assessment factor when evaluating the distributive spatial effects green spaces on quality of life. A set of accessibility measurement approaches are defined to assess the accessibility, such as ‘container’ measurement, ‘coverage’ measurement,’ minimum distance’ approach, ‘travel (summarised by Zhang et al, 2019 ), and ‘residential proximity’ metrics and ‘cumulative opportunity’ metrics (reviewed by Ekkel and de Vries, 2017 ). Ekkel and de Vries (2017) address the association between the green space accessibility metrics and the health aspects, and they conclude that the green spaces within a walkable distance have a positive effect on human health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Eva Heinen et al pointed out that people prefer walking or cycling in paths with beautiful and greenerycovered scenes [40] . Studies also confirmed that physical activities in green spaces bring about more health benefits than activities 住地和公园绿地之间的欧氏距离或网络距离 [38] ,或通过网络地图的API 接口获取出行时间值。可视性指的是居民通勤出行时或者其住宅附近 绿地的可视情况,通常借助调研问卷的自我报告形式或Google地球街景 模式等方式获取 [36] 。 不同的"暴露"指标的选取,一定程度上依赖于城市绿地对人群 健康的作用途径 [7] happened in other (such as indoor) environments [1] . Moreover, along with physical activities, risks of chronic and metabolic diseases, e.g., cardiovascular diseases known as the "No.1 killer worldwide," could be decreased [11] .…”
Section: Physical Activity Encouragementmentioning
confidence: 74%
“…Availability refers to the total area or proportion of the green spaces, or the average NDVI within a defined spatial distance [37] . Accessibility is the distance or time spent from residence to parks, which can be estimated by the Euclidean Distance or network distance by ArcGIS or travel times via API data from digital maps [38] . Visibility represents the green spaces that can be seen visually when residents commute or move around the residential communities, which are usually accessed from self-reports or Google Earth Street View [36] .…”
Section: Exposure Of Urban Green Spaces and Public Healthmentioning
confidence: 99%
“…For example, Sun et al [ 22 ] recorded the complete actual walking routes of 3637 metro users from station exits to their destinations, revealing that the shortest path was cut off because of gated communities. From the perspective of the relationship between human beings and the environment, Zhang et al [ 23 ] explored the influence of the existence of gated communities on the allocation of green resources in cities by revisiting an increasingly popular Gaussian-two-step floating catchment area model. Ozdemir and Turkseven Dogrusoy [ 24 ] further argued that gated communities undermine the relationship between humans and the environment and cause significant handicaps in terms of public life and the sustainability of open public spaces.…”
Section: Literature Reviewmentioning
confidence: 99%